Horizonte político de la religión en perspectiva de la democracia (2019)
Politics and religion in the western culture, in the perspective of democracy and from the horizon of christianism, have been closely interwined, because both depend on how mankind see himself and the world around him. However, one of the main characteristics of democracy, the most commonly accepted political system in the world nowadays, is its secularization. Democracy does not allow thrones, and the religion has been reduced to one of many possibilities that individuals may choose as a way of living their lives. Next, the whole political system implies a different religion and vice versa. Democracy is not, in fact, the moment of the end of religion, but a complete reshaping of the religious experience that could become the more authentic of all. To examine the mutual dependence between politics and religion from the worldview that humanity has upon himself in the context of democracy assuming the proposed challenge to religious freedom from a political horizon that sets as task the guidance towards peace.